Peningkatan Hasil Belajar Matematika melalui Model Double Loop Problem Solving Siswa di Kelas VII-A - Maya Sumiati (DIKDAS MATAPPA: Jurnal Ilmu Pendidikan Dasar, 2023)
The aim of the research was to improve student learning outcomes in class VII-a social arithmetic material at SMPN 1 Cimenyan. This research is made by improve student learning processes and outcomes in learning mathematics and applying a learning approach to build students active in their own knowledge and develop skills in solving problems. The formulation of the problem from this study is described in the form of a question, namely "can the double loop problem solving model improve student learning outcomes in learning mathematics in class VII-A SMPN 1 Cimenyan on social arithmetic material? Based on the conclusions of this study, this model can improve student learning outcomes in learning mathematics on social arithmetic material. This is evidenced by an increase in learning outcomes from cycle 1 to cycle 2. Student learning outcomes in cycle 1 reached an average of 73 with a completeness of 73%. Whereas in cycle 2 student learning outcomes reached an average of 82 with completeness of 93%. Overall it can be concluded that there has been an increase in student learning outcomes in learning mathematics in class VII-A SMPN 1 Cimenyan on social arithmetic material by an average of 9 and 20% in completeness.